Resurrection (2021)
The article offers examples of the theme of resurrection—being raised from the dead—appears throughout the Bible, but it is especially pronounced in the New Testament, which include the life of the child came into him again in KINGS 17:21-22.
Keywords: Bible. New Testament; Resurrection (Jewish theology); Resurrection of Jesus Christ